2014
DOI: 10.1016/j.ijmyco.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot of the genetic diversity of Mycobacterium tuberculosis isolates in Iraq

Abstract: Iraq is specific in having its own most predominant lineage (SIT1144/T1) which is not found among neighboring countries. The 15-locus MIRU-VNTR can be useful in discriminating M. tuberculosis isolates in Iraq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
3
10
4
Order By: Relevance
“…The highest discrimination for allelic diversity was achieved using MIRU loci 10 and 26 (33.3%), in this work ( h ≥ 0.6), followed by MIRU loci 16 and 31 as the moderate discriminatory (20%). These are the loci previously reported as the most discriminatory in a number of other settings in Iran and elsewhere [10,25–29]. Although the system based on 12 loci is most widely used among different sets of MIRU‐VNTR loci, however, the discriminatory of present study was lower than those of other studies, in which the investigators reported the higher discriminatory yielded by 24 loci MIRU‐VNTR on their isolates [7,13].…”
Section: Discussioncontrasting
confidence: 70%
“…The highest discrimination for allelic diversity was achieved using MIRU loci 10 and 26 (33.3%), in this work ( h ≥ 0.6), followed by MIRU loci 16 and 31 as the moderate discriminatory (20%). These are the loci previously reported as the most discriminatory in a number of other settings in Iran and elsewhere [10,25–29]. Although the system based on 12 loci is most widely used among different sets of MIRU‐VNTR loci, however, the discriminatory of present study was lower than those of other studies, in which the investigators reported the higher discriminatory yielded by 24 loci MIRU‐VNTR on their isolates [7,13].…”
Section: Discussioncontrasting
confidence: 70%
“… 15 Other intermediate TB-burden countries, such as Iran, Iraq, and Turkey reported lower rates of transmission, ranging from 24% to 35.9%, based on classical genotyping methods. 14 , 16 , 17 Nevertheless, the different methodological approaches employed herein – compared with studies conducted in nearby regions – make the process of contextualizing transmission dynamics very challenging. However, strikingly, our data suggest that, transmission of full first-line-resistant MTBC strains leading to extended primary MDR-TB cases is a major factor for the emergence of MDR-TB in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…This is partly attributed to the historical movements to and from Africa since colonial times particularly because movements were not strictly restricted. Studies done in different places in Asian continent have shown presence of confined local [ 52 , 53 ] and predominant ancestral TB strains [ 54 ] whose worldwide spread might indicate their origins. It might signify that despite ancestral origins of TB strains there are microevolutions that are taking place within the MTBC lineages that give rise to new locally evolving strains that share specific signatures [ 53 ].…”
Section: Discussionmentioning
confidence: 99%